2011
DOI: 10.7863/jum.2011.30.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Thoracic Facet Injections

Abstract: We describe a relatively feasible technique for performing thoracic facet joint injections using ultrasound guidance. Further verification of this technique, and modification if applicable, should be performed before directly applying this technique in a clinical practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…US-guided thoracic facet injections have been described by Stulc et al [33] . Using fluoroscopy 3D reconstruction imaging, this cadaveric study showed an 80% success rate of the US-guided procedures.…”
Section: Review Gofeld and Montgomerymentioning
confidence: 99%
“…US-guided thoracic facet injections have been described by Stulc et al [33] . Using fluoroscopy 3D reconstruction imaging, this cadaveric study showed an 80% success rate of the US-guided procedures.…”
Section: Review Gofeld and Montgomerymentioning
confidence: 99%
“…Ultrasound-guided interventional pain procedures have been described for cervical, thoracic, and lumbar facets [36][37][38]. Galiano et al [39] has shown that ultrasoundguided lumbar facet injections were both safe and effective with decreased procedure time and no ionizing radiation exposure for the patient or practitioner and Yun et al [40] demonstrated that the efficacy of ultrasound-guided lumbar facet injections was equal to that of fluoroscopic injections for pain control and return to activities of daily living.…”
Section: Pain Medicinementioning
confidence: 99%
“…On physical examination, patients may experience tenderness with palpation over the affected joint; this pain is exaggerated by spine extension, waxes and wanes with physical activity and is often worse at the end of the day [17]. Definitive diagnosis is made by performing an intra-articular injection of local anesthetic or by selectively anesthetizing the medial branch of the dorsal ramus of the spinal nerves corresponding to the level of the patient's pain [18]. In the past, diagnostic intra-articular injections and medial branch blocks were considered equivalent [17].…”
Section: Organization Of the Reviewmentioning
confidence: 99%
“…Thoracic facets are localized by first identifying T12; after, the vertebral bodies are counted moving cephalad until the joint of interest is identified [18]. Feasibility studies have shown some promise but currently, there are no prospective randomized studies that compare US-guided thoracic facet or medial branch blocks to tr aditional approaches such as CT or FS [18].…”
Section: Thoracic Facet Jointsmentioning
confidence: 99%
See 1 more Smart Citation